A Modified Model for Deflection Calculation of Reinforced Concrete Beam with Deformed GFRP Rebar - Minkwan Ju; Hongseob Oh; Junhyun Lim; Jongsung Sim (International Journal of Polymer Science)
The authors carried out experimental and analytical research to evaluate the flexural capacity and the moment-deflection relationship of concrete beams reinforced with GFRP bars. The proposed model to predict the effective moment of inertia for R/C beam with GFRP bars was developed empirically, based on Branson’s equation to have better accuracy and a familiar approach to a structural engineer. For better prediction of the moment-deflection relationship until the ultimate strength is reached, a nonlinear parameter (k) was also considered. This parameter was introduced to reduce the effect of the cracked moment of inertia for the reinforced concrete member, including a lower reinforcement ratio and modulus of elasticity of the GFRP bar. In a comparative study using six equations suggested by others, the proposed model showed better agreement with the experimental test results. It was confirmed that the empirical modification based on Branson’s equation was valid for predicting the effective moment of inertia of R/C beams with GFRP bar in this study. To evaluate the generality of the proposed model, a comparative study using previous test results from the literature and the results from this study was carried out. It was found that the proposed model had better accuracy and was a familiar approach to structural engineers to predict and evaluate the deflection behavior.